The Implementation of Physics Learning through Online Mode during Pandemic Covid-19 Using Metacognitive Knowledge-based Materials - Abdullah, H.; Malago, J. D.; Arafah, K. (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to analyze the effect of metacognitive knowledge-based physics teaching materials (MKBPTM) on the ability to analyze metacognitive knowledge. These teaching materials were used in online learning during the Covid-19 pandemic. The research employed a post-test only control group design. The participants were divided into two groups: the experimental group consisting of 120 students and the control group comprising 124 students, who came from public senior high schools. The results showed that the MKBPTM experimental group had better learning outcomes than the control class using conventional-based teaching materials (CBPTM). The hypothesis testing results indicate a difference in the average score between the experimental and control groups’ metacognitive knowledge analysis skills (MKAS). The results suggest that MKBPTM has an influence on MKAS compared to CBPTM.